Nociceptive behavior induced by chemotherapeutic paclitaxel and beneficial role of antioxidative pathways - Miao, H; Xu, J; Xu, D; Ma, X; Zhao, X; Liu, L (Physiological research, 2019)
Paclitaxel is used for the treatment of several types of cancers. However, one of the significant limiting complications of paclitaxel is painful peripheral neuropathy during its therapy. In this study we examined the engagement of antioxidative signal pathway of the dorsal root ganglion (DRG) in mechanical and thermal hypersensitivity evoked by paclitaxel. Behavioral test was performed to determine mechanical and thermal sensitivity in rats. Western blot analysis and ELISA were used to examine expression of Nrf2-antioxidant response element (ARE) and superoxide dismutases (SOD); and the levels of products of oxidative stress in the DRG. Our results show that paclitaxel increased mechanical and thermal sensitivity as compared with vehicle control animals. Paclitaxel also impaired Nrf2-ARE and SOD in the DRG and amplified products of oxidative stress, namely 8-isoprostaglandin F2alpha and 8-hydroxy-2'-deoxyguanosine. Systemic administration of SOD mimetic using tempol, antioxidant vitamin C or blocking oxidative pathway using NADPH oxidase inhibitor (GKT137831) attenuated mechanical and thermal hypersensitivity induced by paclitaxel. This inhibitory effect was accompanied with decreases of proinflammatory cytokines (PICs) such as IL-1beta, IL-6 and TNF-alpha in the DRG. In conclusion, the data revealed impairment of Nrf2-ARE and heightened oxidative and PIC signals in the DRG of paclitaxel rats, leading to neuropathic pain. Balancing of reactive oxygen species by supplying antioxidants and/or inhibiting NADPH oxidase appears significant to yield beneficial effects in neuropathic pain conditions after chemotherapeutic paclitaxel.
Keywords: signální transdukce; Signal Transduction; Pain Measurement; Antineoplastic Agents, Phytogenic; fytogenní protinádorové látky; nocicepce; krysa rodu Rattus; Antioxidants; zvířata; neuralgie; antioxidancia; Neuralgia; potkani Sprague-Dawley; Male; paclitaxel; Rats; Nociception; Rats, Sprague-Dawley; Animals; Paclitaxel; mužské pohlaví; měření bolesti